A Comparison of Information Seeking Using Search Engines and Social Networks - Morris, Meredith Ringel; Teevan, Jaime; Panovich, Katrina (Proceedings of ICWSM 2010, 2010)
The Web has become an important information repository; often it is the first source a person turns to with an information need. One common way to search the Web is with a search engine. However, it is not always easy for people to find what they are looking for with keyword search, and at times the desired information may not be readily available online. An alternative, facilitated by the rise of social media, is to pose a question to one's online social network. In this paper, we explore the pros and cons of using a social net-working tool to fill an information need, as compared with a search engine. We describe a study in which 12 participants searched the Web while simultaneously posing a question on the same topic to their social network, and we compare the results they found by each method.